Antimicrobial Mechanisms of Leucocyte- and Platelet Rich Fibrin Exudate Against Planktonic Porphyromonas gingivalis and Within Multi-Species Biofilm: A Pilot Study - Rodríguez Sánchez, Fabio; Verspecht, Tim; Castro, Ana B.; Pauwels, Martine; Andrés, Carlos Rodríguez; Quirynen, Marc; Teughels, Wim (Frontiers in Cellular and Infection Microbiology, 2021)
Leucocyte- and platelet rich fibrin (L-PRF) is an autologous biomaterial used in regenerative procedures. It has an antimicrobial activity against P. gingivalis although the mechanism is not fully understood. It was hypothesized that L-PRF exudate releases hydrogen peroxide and antimicrobial peptides that inhibit P. gingivalis growth. Agar plate and planktonic culture experiments showed that the antimicrobial effect of L-PRF exudate against P. gingivalis was supressed by peroxidase or pepsin exposure. In developing multi-species biofilms, the antimicrobial effect of L-PRF exudate was blocked only by peroxidase, increasing P. gingivalis growth with 1.3 log genome equivalents. However, no effect was shown on other bacteria. Pre-formed multi-species biofilm trials showed no antimicrobial effect of L-PRF exudate against P. gingivalis or other species. Our findings showed that L-PRF exudate may release peroxide and peptides, which may be responsible for its antimicrobial effect against P. gingivalis. In addition, L-PRF exudate had an antimicrobial effect against P. gingivalis in an in vitro developing multi-species biofilm.